An Analysis of the Geological Factors Leading to Outburst-Prone Conditions at Collinsville, Queensland - Rogis J (The Australasian Institute of Mining and Metallurgy, 1980)
The basic parameters causing outbursts are rock pressure, gas characteristics and the physico-mechanical properties of the coal. The three sets of factors are to some degree interdependent. At Collinsville, the gas characteristics coupled with the physico-mechanical properties of the coal appear to be the major factors contributing to outbursts. The relative importance of rock pressure is uncertain. The following geological parameters appear to be necessary before outbursts can occur. 1. A coal rank greater than 1.2% vitrinite reflectance. 2. Thrust faults with throws greater than 3.Om or strike- slip faults with coal gouge wider than 0.3m. 3. Seam gas emission values greater than 1.1 cm3 /g. Igneous intrusions are the likely source of the carbon dioxide seam gas. Outbursts have occurred at depths ranging from 215m to 265m. They occur at these relatively shallow depths due to: 1. the high rank of coal at the present topographic surface and the high coalification gradient; 2. the relatively high degree of tectonic deformation of the strata; 3. the seam gas characteristics; and 4. the extent of igneous intrusions.